The Value of Serum Prolidase Activity in Progression of Microalbuminuria in Patients With Type 2 Diabetes Mellitus. Issue 5 (14th December 2015) - Sabuncu, Tevfik; Boduroglu, Omer; Eren, Mehmet Ali; Torun, Ayse Nur; Aksoy, Nurten
Abstract : Background: Prolidase is a cytosolic exopeptidase that plays a pivotal role in collagen turnover. Diabetic nephropathy (DN) is associated with structural changes in glomerular basement membrane accompanied with increased amounts of collagen. Prolidase is known to be abundant in kidney and collagen accumulation is increased in DN, so we aimed to determine the value of serum prolidase activity (SPA) in predicting the progression of nephropathy in type 2 diabetes mellitus (DM). Methods: Thirty type 2 DM patients having microalbuminuria (microalbuminuric group), 30 type 2 DM patients without albuminuria (normoalbuminuric group), and 28 healthy controls (control group) were enrolled. Study groups had similar age, sex distribution, and body mass index (BMI). Results: Metabolic parameters, SPA and urinary microalbumin were determined. SPA was significantly higher in microalbuminuric group when compared with normoalbuminuric and control groups ( P = 0.05 and P < 0.001, respectively). Triglyceride levels were significantly higher and high density lipoprotein cholesterol (HDL‐C) levels were significantly lower in microalbuminuric group compared to control group (Both P < 0.05). SPA showed a negative correlation with HDL‐C level and a positive correlation with urinary albumin excretion (r = –0.219, P < 0.05 and r = 0.39, P < 0.001 respectively). In regression analysis, albumin excretion was the sole parameter influencing SPA. Conclusion: SPA appears to be higher in type 2 DM patients having microalbuminuria compared to patients without microalbuminuria and healthy controls. The pathophysiological role and the significance of SPA in predicting DN need to be further evaluated.